Educação escolar em um Quilombo de Várzea na Amazônia Paraense: lutas e desafios (2018 – 2022) - MELO, Valdenira Silva de (Universidade Federal do Oeste do Pará, 2024)
The research that resulted in this dissertation deals with Quilombola School Education. The study site was Quilombo Saracura, in the municipality of SantarÈm, an Amazon floodplain region, whose uniqueness is significant because it is land that is flooded for a long period of the year, greatly affecting the way of life of its inhabitants. The general objective was to understand the difficulties and pedagogical challenges at Escola Nossa Senhora do Livramento in the period 2018-2022. In 2018, the school collapsed, bringing major reconstruction challenges in both the physical structure and pedagogical issues, leading teachers, students, the management team and other professionals to create alternative strategies for the continuity of education provision, due to the health crisis. Covid-19 and issues arising from policies put into practice by the Brazilian government. The investigation led to the formulation of the following problem: What are the difficulties and pedagogical challenges of School Education at the V·rzea Nossa Senhora do Livramento School, Quilombo Saracura, in SantarÈm-Par·, with the intensification of conservative neoliberal policy in the period from 2018 to 2022? The research is configured in the bibliographical and documentary type, combined with fieldwork procedures, having as a theoretical methodological reference historical-dialectic materialism in dialogue with Ethnography and with theories in which the themes of Rural Education, territoriality and issues are present. related issues, such as: dialogue with Black Epistemologies and between class and race, fundamental for understanding and acting in education from an anti-classist, anti-capitalist and anti-racist perspective. The results indicate the precariousness of teaching work, since more than 90% of employees are temporary employees, in addition to contradictions with Rural Education at Quilombo Saracura. It was possible to identify an alignment with neoliberal policies and agendas, which has contributed, in the local context, to the weakening of specific public policies. Despite the efforts of individuals who work in public education, in order to implement Quilombola School Education in the municipal network, there is still no specific school curriculum that favors debate and the construction of knowledge focused on the African and Afro-Brazilian matrix. Brazilian. The research also highlighted neglect, exclusion and abandonment of formally established education, especially when aimed at the black and quilombola population. The invisibility of black people in terms of access to knowledge education; contributed to the deepening of the exploitation of the workforce of this population, which, in the midst of the degrading slave, capitalist and racist system, has always resisted in an active and articulated way, throughout history. In this way, it is understood that such difficulties need to be faced and overcome, so that it is possible to carry out the challenge of making the school an instrument of social and racial transformation, providing plural dialogues, which contribute to the construction of knowledge and identity. cultural in/of the place where it is located.